Validation of the Composite Autonomic Symptom Score 31 (COMPASS 31) for the assessment of symptoms of autonomic neuropathy in people with diabetes. Issue 6 (19th January 2017) - Greco, C.; Di Gennaro, F.; D'Amato, C.; Morganti, R.; Corradini, D.; Sun, A.; Longo, S.; Lauro, D.; Pierangeli, G.; Cortelli, P.; Spallone, V.
Abstract: Aim: To validate the Composite Autonomic Symptom Score (COMPASS) 31, in its Italian version, for the diagnosis of diabetic cardiovascular autonomic neuropathy in a clinic‐based, single‐centre study. Methods: A total of 73 participants with diabetes (age 55 ± 14 years) completed the COMPASS 31 questionnaire before undergoing cardiovascular autonomic neuropathy and diabetic polyneuropathy assessment according to cardiovascular reflex tests, neuropathic symptoms and signs, and vibration and thermal thresholds. Results: The COMPASS 31 total weighted score differed between participants with and without cardiovascular autonomic neuropathy (29.9 ± 19.5 vs 16.1 ± 14.7; P = 0.003) and with and without diabetic polyneuropathy (28.9 ± 19.1 vs 12.7 ± 11.3; P < 0.0001). It was related to cardiovascular reflex tests score (rho = 0.38, P = 0.0013) as well as diabetic polyneuropathy symptoms (rho=0.61, P < 0.0001) and signs scores (rho = 0.49, P < 0.0001). Receiver‐operating curve analysis showed a fair diagnostic accuracy of total score for cardiovascular autonomic neuropathy (area under the curve 0.748 ± 0.068, 95% CI 0.599–0.861) and diabetic polyneuropathy (area under the curve 0.742 ± 0.061, 95% CI 0.611–0.845). The best score thresholds were 16 for early cardiovascular autonomic neuropathy (sensitivity 75.0%, specificity 64.9%, positive predictive value 37.5% and negative predictive value 90.2%), and 17 for both confirmed cardiovascular autonomic neuropathy and diabetic polyneuropathy (sensitivity 70.0% and 65.5%, respectively; specificity 66.7% and 79.5%, respectively; positive predictive value 25.0% and 67.9%, respectively; and negative predictive value 93.0% and 77.8%, respectively). COMPASS 31 had a good internal consistency according to Cronbach's α coefficient of 0.73. Conclusions: COMPASS 31 can represent a valid, easy‐to‐use, quantitative assessment tool for autonomic symptoms in diabetic neuropathy, with a fair diagnostic accuracy for both cardiovascular autonomic neuropathy and diabetic polyneuropathy. What's new?: Current guidelines recommend the assessment of autonomic symptoms in people with diabetes, but the questionnaires validated to this end are rare or tricky to use. COMPASS 31 is an easier, shorter, 31‐item version of COMPASS, developed from the Autonomic Symptom Profile. This study provides the first validation of COMPASS 31 for diabetic cardiovascular autonomic neuropathy (CAN): total weighted COMPASS 31 score was associated with CAN, correlated with heart rate cardiovascular reflex tests, and had a fair diagnostic accuracy for CAN with a sensitivity and a specificity of 75% and 65%, respectively. Rather unexpectedly, COMPASS 31 also had an acceptable diagnostic performance for diabetic polyneuropathy. COMPASS 31 is an easy and reliable assessment tool for autonomic symptoms of diabetic neuropathy, open to possible clinical use as a screening tool for CAN.